Low cardiorespiratory and mitochondrial fitness as risk factors in viral infections: implications for COVID-19 - Burtscher, J.; Millet, G. P.; Burtscher, M. (British Journal of Sports Medicine, 2021)
Physical activity (PA) modulates immune system functions. Susceptibility to viral infection thereby depends on the volume and intensity of PA: regular moderate PA (up to 60% of maximal oxygen uptake for no more than 1 hour/session) and an associated high cardiovascular fitness (CRF) boost immune system capacity and reduce inflammation, whereas exhausting PA transiently suppresses immune functions.